Information technology project management - Schwalbe, Kathy (Course Technology Cengage Learning, 2011)
Information is traveling faster and being shared by more individuals than ever before. Managing Information Technology Projects, REVISED 6E, International Edition offers the "behind-the-scene" aspect of technology. Although project management has been an established field for many years, managing information technology requires ideas and information that go beyond standard project management. By weaving together theory and practice, this text presents an understandable, integrated view of the many concepts skills, tools, and techniques involved in project management. Because the project management field and the technology industry change rapidly, you cannot assume that what worked even five years ago is still the best approach today. This text provides up-to-date information on how good project management and effective use of software can help you manage projects, especially information technology projects. Managing Information Technology Projects, REVISED 6E, International Edition, is still the only textbook to apply all nine project management knowledge areas: project integration, scope, time, cost, quality, human resource, communications, risk, and procurement management.